Concepções dos professores de português sobre surdez e aluno surdo num curso de formação continuada - Furlan, Luciana Aparecida (2011)
One of the issues related to the construction and consolidation of a truly inclusive school concerns the importance of teachers, their valorization and their training, both initial and continued in the form of graduate specialization, update courses and short term courses. The objective of this work, considering the above context, was to determine whether teachers' conceptions of Portuguese, referring to his deaf students, have been changed after attending a continuing education course entitled Portuguese Language for the Deaf. The study was conducted at a Board of Education located in the central region of São Paulo State, which offered the course in the period 2004 to 2008, and focused on the year 2005. Study participants were 33 teachers who took part of course in Portuguese Language for the Deaf in 2005 and responded to assessments of the same period. The research, which consisted of a study of descriptive and exploratory qualitative approach was used to document analysis and semistructured interviews. Data analysis employed the procedures of content analysis. The writings of the teachers revealed some misconceptions about deafness, the deaf students and their learning. They also revealed the contributions of the course concerned that these contributions have been revised. The survey also offered some reflections on the issues surrounding the initial training and continuing education, the complexity of teaching Portuguese for the deaf and the points that could be improved in the course examination.